Pelaksanaan Dan Evaluasi Dakwah Pimpinan Daerah Al Jam’iyatul Al Washliyah Dalam Mengatasi Maraknya Penyalahgunaan Narkoba di Kota Tanjung Balai - Andini Andini; Winda Kustiawan (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2025)
Drugs are a serious threat to diversity and social stability, so structured da'wah implementation and evaluation are needed to overcome it. This study aims to determine how the implementation and evaluation of the da'wah of the Regional Leadership of Al Jam'iyatul Al Washliyah in overcoming drug abuse in Datuk Bandar District, Tanjung Balai City. The approach used is qualitative with field methods through observation, interviews, and document analysis. The results showed that the implementation of da'wah was carried out through various activities such as futsal tournaments, canoe rowing competitions, da'wah syiar, silat training, and cooperation with BNN for urine tests. Evaluation is carried out by assessing participation, behavior change, and program effectiveness. This activity is proven to contribute in providing education and increasing public awareness of the dangers of drugs.